Evaluation of renal vasculature and its variants by CT angiography - Bala Murali Krishna Patibandla,; Mriganka Deuri Bharali,; Ershad Hussain Galeti,; Saqib Shahab, (Asian Journal of Medical Sciences, 2022)
Background: Kidneys are a pair of retroperitoneal organs supplied by a single renal artery and vein. However, the classic illustration of the renal vasculature, formed by one renal artery and one renal vein, occurs in ≤25% of cases. MDCT angiography is presently the most preferred investigation for assessing prospective renal donors. Aims and Objectives: This study aims to familiarize urologists with the variations found in the renal vascular system, emphasizing prevalence, the adequate, appropriate terms, and the clinical and surgical implications involved. Materials and Methods: A cross-sectional study in 50 patients clinically indicated to undergo CT Renal angiographic study over 2 years is included in the study. This study was carried out to look for any anatomical variants in renal vasculature. CT examination was performed on a multidetector 16 slice CT Siemens scanner in the department of radiodiagnosis. Once conventional CT is done, the data obtained can produce 3D post-processing images that simulate conventional angiograms. Results: Out of 50 patients, single renal arteries are present in 27, and multiple renal arteries are present in 23 patients. Out of 27 patients with single renal arteries, 22.2 % has perihilar arterial branching. The most common variant was accessory renal arteries, which are found in 56% of individuals, followed by aberrant renal arteries found in 30% of individuals. Double renal arteries are found in 8.7% and triple renal arteries in 4.3% of cases. Out of 50 patients, 48 patients have a single renal vein, whereas two patients have supernumerary veins. The present study found right renal vein duplication in only 2% of patients. Conclusion: Renal arteries and veins show numerous variations in their origin sites, numbers, course, and division patterns. These variants exist in the population with high prevalence and are thus crucial in preoperative and intra-operative analysis for better prognosis and reduced complications. Preoperative CT evaluation of renal vasculature using MDCT angiography helps depict the presence or absence of renal arterial and venous variants.